Improving detection of familial hypercholesterolaemia in primary care using electronic audit and nurse‐led clinics. Issue 3 (26th November 2015) - Green, Peter; Neely, Dermot; Humphries, Steve E.; ,; Saunders, Tanya; Gray, Val; Gordon, Louise; Payne, Jules; Carter, Slade; Neuwirth, Clare; Rees, Alan; Gallagher, Hazel
Abstract: Rationale, aims and objectives: In the UK fewer than 15% of familial hypercholesterolemia (FH) cases are diagnosed, representing a major gap in coronary heart disease prevention. We wished to support primary care doctors within the Medway Clinical Commissioning Group (CCG) to implement NICE guidance (CG71) and consider the possibility of FH in adults who have raised total cholesterol concentrations, thereby improving the detection of people with FH. Methods: Utilizing clinical decision support software (Audit+) we developed an FH Audit Tool and implemented a systematic audit of electronic medical records within GP practices, first identifying all patients diagnosed with FH or possible FH and next electronically flagging patients with a recorded total cholesterol of >7.5 mmol L −1 or LDL‐C > 4.9 mmol L −1 (in adults), for further assessment. After a 2‐year period, a nurse‐led clinic was introduced to screen more intensely for new FH index cases. We evaluated if these interventions increased the prevalence of FH closer to the expected prevalence from epidemiological studies. Results: The baseline prevalence of FH within Medway CCG was 0.13% (1 in 750 persons). After 2 years, the recorded prevalence of diagnosed FH increased by 0.09% to 0.22% (1 in 450 persons). The nurse advisor programme ran for 9 months (October 2013–July 2014) and during this time, the recorded prevalence of patients diagnosed with FH increased to 0.28% (1 in 357 persons) and the prevalence of patients 'at risk and unscreened' reduced from 0.58% to 0.14%. Conclusions: Our study shows that two simple interventions increased the detection of FH. This systematic yet simple electronic case‐finding programme with nurse‐led review allowed the identification of new index cases, more than doubling the recorded prevalence of detected disease to 1 in 357 (0.28%). This study shows that primary care has an important role in identifying patients with this condition.